Anti-Diabetic and Antioxidant Activities of Red Wine Concentrate Enriched with Polyphenol Compounds under Experimental Diabetes in Rats - Mariya Sabadashka; Dariya Hertsyk; Paulina Strugała-Danak; Anita Dudek; Olena Kanyuka; Alicja Z. Kucharska; Leonid Kaprelyants; Nataliia Sybirna (MDPI AG, 2021)
We obtained red wine concentrate, which was enriched with natural polyphenolic compounds (PC concentrate). The main purpose was to study the hypoglycemic and antioxidant effects of the red wine concentrate, and its impact on key hematological parameters of rats with experimental diabetes mellitus. While administrating the red wine concentrate to rats with diabetes, partial recovering of glucose tolerance was promoted, as well as normalization of glycated hemoglobin level, an increase in the quantity of erythrocytes and hemoglobin concentration. PC concentrate had anti-radical effect, which was determined using 2,2-diphenyl-1-picrylhydrazylradical (DPPH) method and effectively inhibited oxidation of phosphatidylcholine liposomes, induced by 2,2'-azobis(2-amidinopropane) dihydrochloride (AAPH) as a free radical generator. It was also confirmed that PC concentrate had antioxidant properties in vivo. The contents of lipid peroxidation and protein oxidation products, the activity of catalase, and glutathione peroxidase (GPx) were increased in the plasma of rats with diabetes mellitus. At the same time, the activity of superoxide dismutase (SOD) was decreased. The concentrate of red wine had a corrective effect on investigated indicators and caused their normalization in plasma of diabetic animals.